Enforcement of Competition Law on Digital Platforms – Responsive Modelling for Digitization Challenges under the EU Law - Margvelashvili, Tamta (Journal of Law, 2023)
The law of the European Union (hereinafter the “EU") is a complex legal system that builds supranational law on the basis of comparative studies.[1] For the EU the harmonization of law is one of the instruments that ensures the proper functioning of the EU internal market and achieves the idea of perfecting European integration, which has long gone beyond its current geographical boundaries to include the "Third World".[2] Accordingly, the harmonization of competition law is not only an endeavor for EU member states to develop a unified system to ensure effective competition, but it is also a basic tool for countries on the path to EU membership. This particular paper is focused on these important issues. It by directing its attention on the root of harmonization of EU competition law enforcement, presents the possibilities of competition enforcement mechanisms legal transfer for digital platforms from one jurisdiction to another based on a comparative method. Therefore, the first research object of the article is the normative and case law trends of the European Union, that ensure the enforcement of fair competition for digital platforms in the continuous process of digitization. On the other hand, the focus is shifted towards the prospects of harmonization of competition law enforcement tools for digital platforms in Georgia. [1] Vranken M., Fundamentals of European civil law. Blackstone Press, London, 1997, 14. [2] The term is used to refer to a country that is not a member of the European Union. Citizens do not enjoy free movement within the EU according to Article 2(5) of EU Regulation 2016/399 (Schengen Code).